KINERJA AKADEMIK PASCA SERTIFIKASI AUN-QA PADA PROGRAM STUDI DI INSTITUT PERTANIAN BOGOR - Adelyna Adelyna; Anas Miftah Fauzi; Ahmad Juanedi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The aims of the research are to evaluate the academic performance progress of the six study programs of IPB after the certification of AUN-QA. The research was a case study in six study programs that had been certified by AUN-QA until December 2014. This research was conducted with the objectives of defining the relevant indicators of BSC IPB and AUN-QA criteria, analyzing the criteria values of AUN-QA after the AUN-QA certification, analyzing the academic performance based on KPI BSC after the AUN-QA certification, and analyzing the problems in improving academic performance as the basis for the formulation of strategies for improving academic quality. The method used in this research was the balanced scorecard approach (BSC). The results showed that the certification of AUN-QA contains 15 relevant criteria and supports the achievement of BSC IPB. Key performance indicators (KPI) BSC IPB supported by the AUN-QA criteria consist of 21 of the 33 indicators of BSC IPB, and 14 of them are relegated to the BSC department indicators. The AUN-QA criteria values on the study program have increased with the highest criterion value in student quality and the lowest one in support staff quality. The weak criteria required to be improved include support staff quality, student assessment, stakeholder feedback, and program specification.Keywords: AUN-QA certification, academic performance, balanced scorecard